Trueman's Specific series UGC-CSIR NET for JRF/Lectureship Compulsory paper- 1 (Common for Science Subjects) - Sunil Kushwaha (Trueman's Specific series, 2015)
UGC - CSIR JRF/NET : Compulsory Paper 1 is a comprehensive book for candidates appearing for National Eligibility Test for science subjects. The book comprises of chapters on Reasoning and Quantitative Aptitude, Logical Reasoning, Data Interpretation, Graphical Analysis, Analytical Reasoning, Numerical Ability and Puzzles. In addition, there are several solved and unsolved questions for final practice and revision. This book is essential for undergraduates students of science aspiring to get Junior Research Fellowship in Indian Universities. About Trueman Book Company Trueman Book Company was established in 1986. It is one of the leading academic publishers of India. They produce books on a wide range of subjects including sciences, humanities and engineering. They have produced books like Elementary Biology, Trueman's UGC NET National Eligibility Test/SET State Eligibility Test English Literature 1st Edition, etc.